The transition from enthesis physiological responses in health to aberrant responses that underpin spondyloarthritis mechanisms - Aydin, Sibel Zehra; Bridgewood, Charles; Zabotti, Alen; Girolimetto, Nicolò; McGonagle, Dennis (Current opinion in rheumatology, 2021)
Despite immunology and translational therapeutics advances in inflammatory arthritis over the past two decades, the enthesis, which is the epicentric of the spondyloarthritis family pathological process, retains many mysteries because of tissue inaccessibility that hampers direct immune study. As entheses are subject to almost continuous mechanical stress and spondyloarthritis is linked to microdamage or injury and joint stress, it is cardinal to understand the physiological changes occurring within the entheses not only to be able to differentiate disease from health but also to understand the transition normal physiology break down and its merges into spondyloarthritis-related disease. Imaging has played a major role in understanding the enthesis in human. Remarkable insights from enthesis functioning and microdamage in normal and with ageing including those linked to body mass index is emerging. The impact of mechanical stress and degenerative conditions on the development of the secondary entheseal vascular changes is not understood. Of note, ultrasound studies in psoriasis have shown higher power Doppler changes compared to controls pointing towards a role for vascular changes in the development of enthesitis in psoriatic arthritis. The literature pertaining to normal entheses changes with age, microdamage and vascular changes in health is providing a roadmap for understanding of the enthesis and its potential role in evolution of spondyloarthritis including psoriatic arthritis.